ENCOURAGMENT OF ARTISTIC CREATIVITY OF STUDENTS IN THE ZONE OF PROXIMAL DEVELOPMENT - Popadić, Marko (Sociološki godišnjak, 2023)
The goal of the study is to experimentally examine the possibility of encouraging artistic creativity in the zone of proximal development. Cooperation with the more competent person enables the pupils to solve more complex tasks more successfully than they would independently, thereby practicing those functions. This progress was monitored before and after the assignment of visual, verbal, and auditory levels of assistance during the solving of art tasks. The instrument used is an adapted version of the LV1 test. The participants were pupils in the sixth grade of elementary school in Trebinje. The results of the research indicated that the pupil showed improvement in all tasks and it was much easier to do the testing after the experimental program which was designed to monitor the zone of proximal development. These results are considered in the context of Vygotsky’s theory. The paper discusses the theoretical and practical implications and possibilities of encouraging artistic creativity in the zone of proximal development.
Keywords: encouragement of artistic creativity; zone of further development,; art assignments; cooperation